Estimation of the amount of sediment entering into Shumburit reservoir from the Shumburit watershed, East Gojjam zone, Amhara Region, Ethiopia - Lake Endalew; Arega Mulu (Environmental Challenges, 2023)
Sediment accumulation is a major factor in reducing a reservoir's useful life. As a result, information on any changes in storage capacity is required to reduce the reservoir's risk. Therefore, the goal of this study was to determine the amount of sediment entering the reservoir using the Modified Universal Soil Loss Equation (MUSLE). The sediment entering into the reservoir was calculated by the MUSLE model over the last six years and is estimated after determining the physical parameters (K, LS, C, and P factors) and runoff index (VQ and QP) from the watershed using ArcGIS 10.8 and Excel software. The single event sediment (daily sediment) using MUSLE was a product of physical parameters (K, LS, C, and P factors) and runoff index (VQ and QP). The Modified Universal Soil Loss Equation estimated 256,262.86 tons of sediment yield at the outlet of the watershed (inflow to the reservoir in the last six years). The reservoir's total capacity has been reduced by 5.4 percent over the last six years of operation. The average rate of sedimentation was estimated at 42,710.48 tons/year or 31.64 tons/ha/year. Hence; the annual capacity reduction of the reservoir was 0.9 percent.